Electronic Arbitration to Settle Disputes in E-commerce Contracts - Agouni , Mohammed (Journal of Legal Studies and Researches, 2023)
This study examines the legal regulatory framework for electronic arbitration as a means of dispute settlement, as it is based on departing from the usual methods of litigation and the procedures that follow and the time it takes, which may not be permitted by the circumstances of some transactions, especially commercial contracts. Electronic arbitration does not differ from traditional arbitration, except through the means by which arbitration procedures take place in the virtual world, where there is no paper, traditional writing, or the physical presence of people, which provides additional features that are in line with the nature of transactions that take place in the virtual environment, and therefore it is important to address how the arbitrators are appointed, clarify the controls for the conduct of litigation procedures, and determine the law applicable to the arbitration agreement, especially as we are witnessing the spread and expansion of electronic transactions that led to an increase in the request for resort to this type of arbitration.